A facilitator model for the use of history of science in science teaching - (:unkn) unknown (My University, 2011)
This paper proposes a theoretical model for science educators to promote science teachers' use of the history of science in science teaching. The practical perspective of the research on the use of history of science does not provide consistent evidence to support a model to explain why and how history of science is influential in science education. In this paper, a theoretical model is discussed relying on empirical findings of the research and educational theories. The facilitator model was developed through a review of the literature that discusses the relationship between history of science and science education and a previous study that used history of science in eighth grade science lessons. The model defines four different levels: Interest Level, which includes information about stories of scientists' lives to humanize science and scientists and to catch students' interest in science lesson; Sociocultural Level, which includes information about how science interacts with society to improve students' attitudes towards science and to humanize science; Epistemological Level, which includes information about scientific methods followed by scientists in the history to introduce some concepts of scientific inquiry; and Conceptual Level, which includes information about historical development of the concepts to help students understand scientific concepts. This model may serve to yield theory-based discussions on the relationship between history of science and science education.
Keywords: History of Science; Science education; Science teaching